An android application and speech recognition-based IoT-enabled deployment using NodeMCU for elderly individuals - Arunav Mallik Avi; Md. Sohel Rana; Mustakim Billah Bedar; Md. Asif Talukder (Bulletin of Electrical Engineering and Informatics, 2023)
The internet of things (IoT) is the trendiest technology in the computing, Embedded and modern control systems industries. An efficient IoT-enabled home automation technique that allows users to remotely control home appliances and observe sensor data from a long distance via internet connectivity. This study identifies a smart approach to assisting any user, particularly elderly individuals, to control home appliances and monitor home weather conditions using an Android application and voice command using speech recognition. Multiple specialized microcontrollers, especially NodeMCU and other components like sensors, networks, relays, fans, lights and android devices are used to implement this proposed system. This IoT platform device is configured to recognize the instructions from the Android application to control appliances as well as compute real-time weather data from sensor and upload the sensor data stream to the IoT web server. The dedicated IoT web server, that is accessible by the Android application for further IoT operations. On the other hand, the Google Speech to Text (STS) service enables a facility to control home appliances through voice command. Mobility issues plague the elderly, complicating even the simplest tasks. From observation of this research, they can control this proposed system without ever touching any physical switches.